Infection Rates Following Buttonhole Cannulation in Hemodialysis Patients. Issue 5 (17th March 2016) - Collier, Sophie; Kandil, Hala; Yewnetu, Enat; Cross, Jennifer; Caplin, Ben; Davenport, Andrew
Abstract: Arteriovenous fistula (AVF) is the preferred access for hemodialysis (HD). Buttonhole (BH) needling has increased following the introduction of "blunt" fistula needles. Although some reported advantages for BH needling, others have reported increased infection risk. As such we reviewed our center practice, and the effect of both nasal screening and eradication and re‐education and training programs. We audited the outcomes of 881 HD patients dialyzed between November 2009 and May 2012, divided into three groups: 175 dialyzing exclusively by central venous catheter (CVC), 478 exclusively by area needling AVF (AVF) and 219 by BH. There were 31 Staphylococcus aureus bacteremias (SABs); 14 (45.2%) dialyzing with CVCs, 12 (38.7%) BH and five (16.1%) AVF. The 30 day mortality rate for SAB was 7.5% with a complication rate of 22.6%. The hazard ratio for first SAB was significantly greater for both CVC and BH access compared to AVF (5.3 (95% CI –1.9–18.6), P <  0.001 and 3.6 (1.3–96), P =  0.011, respectively). During the study SAB rates per 1000 CVC days were 0.21, compared to 0.15 for BH. After major re‐education and asepsis technique campaigns the SAB rate for BH fell to 0.06, but quickly returned to 0.17. Extending BH needling to all our dialysis centers, SAB infection rates increased to those not dissimilar to CVC access. Despite re‐education programs coupled with a strict asepsis policy and active SA eradication, followed by audit cycles, the increased infection risk with BH remained, such that we have limited BH to self‐care patients.